2006
DOI: 10.1002/jcb.21083
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl‐hydroxylase inhibition and HIF activation in osteoblasts promotes an adipocytic phenotype

Abstract: Bone is a dynamic environment where cells sense and adapt to changes in nutrient and oxygen availability. Conditions associated with hypoxia in bone are also associated with bone loss. In vitro hypoxia (2% oxygen) alters gene expression in osteoblasts and osteocytes and induces cellular changes including the upregulation of hypoxia inducible factor (HIF) levels. Our studies show that osteoblasts respond to hypoxia (2% oxygen) by enhancing expression of genes associated with adipocyte/lipogenesis phenotype (C/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 72 publications
1
32
1
Order By: Relevance
“…On the other hand, recent reports suggest that PHDs have other functions, such as in cellular homeostasis independently of oxygen availability. For example, phenotypic changes from osteoblasts to adipocytes were observed under hypoxic conditions, and PHDs, especially PHD2 and 3, were implicated in the mediation of this response (14). In studies reported by Floyd et al (13), it was found, using a murine 3T3-L1 adipocyte model, that PHD inhibition prevented adipocyte formation under normoxia and that the relative expression of PHD isoforms differed during the progress of adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recent reports suggest that PHDs have other functions, such as in cellular homeostasis independently of oxygen availability. For example, phenotypic changes from osteoblasts to adipocytes were observed under hypoxic conditions, and PHDs, especially PHD2 and 3, were implicated in the mediation of this response (14). In studies reported by Floyd et al (13), it was found, using a murine 3T3-L1 adipocyte model, that PHD inhibition prevented adipocyte formation under normoxia and that the relative expression of PHD isoforms differed during the progress of adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Orig-inally, PHD was considered a regulator of HIF-1␣, but recent reports suggest that it participates in differentiation independently of hypoxic status and in cellular homeostasis. For example, under normoxic conditions, all three PHDs increased throughout adipogenesis, and pharmacological inhibition of PHD activity abrogated adipocyte differentiation and reduced the expressions of all three PHDs (13), and dimethyloxalyl glycine (DMOG, a PHD inhibitor) caused osteoblasts to adopt adipocytic phenotypes (14). Fu et al (15) reported that PHD3 regulates skeletal muscle differentiation by modulating the stability of myogenin protein, a known key player in myogenic differentiation.…”
mentioning
confidence: 99%
“…In another example, PHDs were shown to be important for the maintenance of osteoblast identity, because inhibition of PHD activities with DMOG caused osteoblasts to adopt adipogenic phenotypes. 68 We have recently investigated roles of PHDs in mice. While Phd1 À/À or Phd3 À/À mice survive normally, Phd2 À/À embryos die at mid-gestation stages.…”
Section: Biological Functions Of Phdsmentioning
confidence: 99%
“…However it has been well documented that bone can survive 6-12 hours of impaired blood flow before sustaining irreversible damage, but both bone formation as measured by osteocalcin and bone resorption as measured by N-telopeptide (Ntx) are adversely altered under hypoxic condition. 22,23,24,25 For these mechanisms to account for aseptic necrosis (in the absence of or in conjunction with decompression related bubbles), they should either produce perfusion limiting effects that last beyond the immediate time frame of compression, have additive effects that do not resolve by the next exposure, or both.…”
mentioning
confidence: 99%